Electroconvulsive therapy: 80 years old and still going strong - Gazdag, Gábor (World J Psychiatry, 2019)
Electroconvulsive therapy (ECT), which is among the oldest and most controversial treatments in the field of psychiatry, has its 80(th) birthday this year. In this brief historical overview, the discovery of the therapeutic effects of convulsive therapy by Laszló Meduna, and the circumstances that motivated Ugo Cerletti and Lucio Bini to use electricity as a means of seizure induction are described. Meduna’s original theory about the antagonism between epilepsy and schizophrenia has been replaced by hypotheses on the mechanism of action of ECT. The position of ECT in modern psychiatry is also discussed with special attention to its most important clinical indications, including catatonia, and pre- and postpartum affective and psychotic states that are responsive to ECT and in which ECT may even be lifesaving. Adverse effects and comparison of ECT with recently developed brain stimulation methods are also reviewed. The negative media portrayal of ECT and its earlier misuse may have contributed to its negative professional and public perceptions indicated repeatedly in attitude surveys. This negative attitude has played an important role in the decreasing use of ECT in the developed world and a reduction in access to ECT, which constitutes a violation of psychiatric patients’ right to an effective treatment.